Konsep Pendidikan Islam Holistik Dalam Memenangkan Persaingan di Era Milenial - Amie Primarni (Jurnal Dirosah Islamiyah, 2019)
This study aims to produce an Educational Concept that is able to win competition in the Mileneal Era. Thisstudy uses a qualitative method with a literature study approach. This research approach uses analysis from theperspective of anthropology, sociology and educational psychology. Using triangulation techniques, the writer triesto construct the construct of a learning concept. In conclusion, the results of this study resulted in a concept of TheFoundation Of Learning Process, a foundation of continuous learning that gradually develops spiritual, intellectual,physical and emotional development abilities, in a planned, structured manner.